Children's street crossing performance when auditory information about traffic is lacking. (February 2021) - Morrongiello, Barbara A.; Corbett, Michael R.; Vander Hoeven, Erin
Highlights: Children are at high risk of injury when crossing streets. Using Virtual Reality technology, measures were taken throughout their crossing. When vehicle sound was absent they initiated crossings more slowly. Slower initiations resulted in more close calls and hits. Abstract: Purpose: The current study examined the impact on children's street crossing behaviors of not having auditory-based information about traffic when crossing streets. Method: Using a fully-immersive virtual reality system, numerous indices of children's street crossing behaviors were measured both when they had auditory-based information about traffic and when this was lacking. Results: The lack of traffic sounds did not influence the inter-vehicle gap size that children crossed into but it did result in slower initiations and, ultimately, more high-risk outcomes (close calls and hits). Conclusion: Traffic sounds significantly contribute to enhance children's safety when crossing streets. Cars with reduced sounds (e.g., electric) and anything that interferes with children accessing auditory-based traffic information (e.g., wearing headphones) could increase their risk of pedestrian injury.